Educação, memória e literatura - Sugai, Beatris de Moura Rocha (2020)
This dissertation investigates the act of storytelling as a supposedly potentially pedagogical element due to its characteristics of deep relationship with issues that refer to the mechanisms of dialogue with literary practice. Literature has characteristic elements that make it one of the main means of reflection on subjective issues that dialogue with the world. Based on the relationship between the act of storytelling and literature, we seek to ascertain a supposed pedagogical function, both through oral communication, which was a predecessor of literary practice through writing, and through the relationship with memory, which enables the act of developing tell the story orally. The perspective that directed and guided these two languages towards education was the thought of educator Paulo Freire, more specifically his category of thought called awareness. The intention of seeking a thought that deals with important issues of education through a means that aims to make the pedagogical processes humanizing is given by the dialogical way that this perspective leads educational practices. We structured our research in a historical chronological process that didactically illustrated how the transition from oral perspective to literary writing took place. The Literature and its development after Ancient Greece was observed until the emergence in the 18th century of a literature that sought a direction to the world of children. After this contextualization of the act of storytelling in relation to the literary world, we started a dialogue with the work of the educator Paulo Freire and with the category of thought that we chose as a theoretical foundation for the relationship between the act of storytelling and the pedagogical practices that dialogue with that language. We verified the possibilities of implementing principles of awareness in the development of activities related to the act of telling stories. Finally, in the last chapter, we elaborated a pedagogical intervention project that brings the possibility of making such a discussion effective at school. The Story Bricks Project was the realization triggered by the studies carried out in the research, which we believe can bring a certain contribution to the pedagogical practice related to the use of literature as the main motivator for dialogue between students, teachers and the community who live around the school. The dialogical act provided by the joint reflection of the subjects involved in the project was the objective of using the act of telling stories as a mediating action in the search for an awareness process.